2008
DOI: 10.1111/j.1445-2197.2008.04618.x
|View full text |Cite
|
Sign up to set email alerts
|

Surgical Site Marking Does Not Affect Sterility

Abstract: Surgical site marking carried out with a non-sterile surgical marking pen did not contaminate the surgical site. We recommend the practice of surgical site marking.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 8 publications
0
4
0
1
Order By: Relevance
“…This may be attributed to differences in solution application in accordance with manufacturer guidelines, as povidone-iodine prep involves painting a single layer without scrubbing and chlorhexidine prep involves repeated forward and backward strokes for 30 seconds [ 18 ]. In 2008, Rooney et al performed an experiment where they cultured forearms that had been marked like a simulated surgical site with a multiply used marking pen and found that there was no bacterial growth following site sterilization with a 10% povidone-iodine solution [ 5 ]. Another experiment used cultured marking pens on surgical sites that were prepped with betadine (povidone-iodine) scrub followed by betadine (povidone-iodine) paint.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This may be attributed to differences in solution application in accordance with manufacturer guidelines, as povidone-iodine prep involves painting a single layer without scrubbing and chlorhexidine prep involves repeated forward and backward strokes for 30 seconds [ 18 ]. In 2008, Rooney et al performed an experiment where they cultured forearms that had been marked like a simulated surgical site with a multiply used marking pen and found that there was no bacterial growth following site sterilization with a 10% povidone-iodine solution [ 5 ]. Another experiment used cultured marking pens on surgical sites that were prepped with betadine (povidone-iodine) scrub followed by betadine (povidone-iodine) paint.…”
Section: Discussionmentioning
confidence: 99%
“…With this study, we aimed to determine the colonization of surgical marking pens in the plastic surgery population. We hypothesized that reusing marking pens, as long as they are stored in a clean environment and patients are prepped after their use, is a safe practice that does not affect surgical site sterility, as this had been previously reported by Rooney et al in 2008 [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…reviewed the available evidence and concluded that surgical site marking does not affect the sterility of the surgical field. [78]…”
Section: Discussionmentioning
confidence: 99%
“…El marcaje sobre la zona donde se va a realizar la cirugía podría presentar un potencial riesgo de infección y por ello que algunos cirujanos optan por marcar «No» en el lado que no se debe operar 36 , pero posteriormente se ha asegurado que la realización de una marca en lugar de la incisión cutánea no ocasiona un aumento del porcentaje de infección 10 . Generalmente, la marca en el lugar a realizar la incisión se realiza con un rotulador no estéril y que suele utilizarse para varios pacientes, pero se ha demostrado que el marcado del sitio quirúrgico llevado a cabo con un marcador quirúrgico no estéril no contamina el sitio quirúrgico y después de la esterilización con una solución yodada no existe contaminación de esta zona 46,47 . También se ha comprobado que el marcado preoperatorio no atrapa bacterias debajo del lugar de la marca por lo que tampoco contamina la herida quirúrgica 48 .…”
Section: Discussionunclassified